It is Monday again: Weekend sleep differentially relates to the workweek via reattachment on Monday - Jette Völker; Monika Wiegelmann; Theresa J. S. Koch; Sabine Sonnentag (Journal of Organizational Behavior, 2024)
The weekend constitutes an important recovery period for employees. However, psychologically reattaching to work on Monday can be difficult because employees must transition from their private to their work role. Building on boundary theory and integrating a sleep and circadian perspective, we shed light on this transition by investigating antecedents and outcomes of Monday reattachment. We propose that three weekend sleep characteristics differentially relate to reattachment on Monday: weekend sleep quality, catch-up sleep (extended sleep duration on the weekend), and social sleep lag (differences in sleep times workweek vs. weekend). Successful reattachment on Monday should, in turn, be related to lower levels of exhaustion and higher task performance during the workweek. We conducted a weekly diary study with 310 employees (9330.167emweeks) over four workweeks. Two-level path models demonstrated that higher weekend sleep quality was indirectly related to lower levels of workweek exhaustion via higher levels of Monday reattachment. In contrast, higher catch-up sleep was related to higher levels of workweek exhaustion via lower levels of Monday reattachment. Accordingly, we demonstrate that Monday reattachment can set the tone for the entire workweek, but the capability to reattach can depend on weekend sleep as a core recovery process.
Keywords: 650; exhaustion; micro-role transition; reattachment; sleep; task performance